PENGUATAN KEBIJAKAN PEMBERDAYAAN SOSIAL EKONOMI RAKYAT ERA NEW NORMAL - Lestari, Ratna Ani (Universitas Wijaya Kusuma Surabaya, 2021)
In this paper, the writer who has been the regional head of Banyuwangi Regency (2005- 2010) is faced with continuous policy making. One of the policies taken is the empowerment program. In the New Normal era, it is necessary to strengthen policies as a socio-economic empowerment of the people due to Covid-19. Local governments by utilizing their regional potentials to make policy innovations, as an economic recovery due to Covid-19 by collaborating with the private sector so that the local economy continues to rotate by involving community participation.Keywords: policy, empowerment, New Normal era